The prognostic significance of circulating plasma cells in newly diagnosed multiple myeloma patients - Yao, Weiqin; Yang, Haifei; You, Hongying; Shang, Jingjing; Zhai, Yingying; Yan, Zhi; Yan, Shuang; Shi, Xiaolan; Yao, Ying; Wang, Jing; Wang, Panfeng; Xu, Yun; et al. (Frontiers in Oncology, 2023)
Objective: Multiple myeloma (MM) is a highly characteristic tumor that is influenced by numerous factors that determine its prognosis. Studies indicate that the presence of circulating plasma cells (cPCs) is a detrimental factor that significantly impacts the prognosis of patients with MM.: This study retrospectively analyzed the prognostic value of cPCs quantified by 10-colour flow cytometry in 145 newly diagnosed MM (NDMM) cases in the First Affiliated Hospital of Soochow University from November 2018 to February 2021. The study was approved by Ethics Committee of the Hospital (2021 No. 93).Results: 99/145 patients (68.2%) were detected cPCs. Through Receiver Operating Characteristics (ROC) analysis, an optimal threshold of 0.165% was identified as a predictor for overall survival (OS). The median progression free survival (PFS) was 33 months in patients with cPCs ≥0.165%, whereas those with cPCs <0.165% had a PFS of less than 33 months (P=0.001). The median OS was not reached for two groups, the 3-year OS for patients with cPCs ≥0.165% was 71% compared with 87% for those with cPCs <0.165% (P=0.003). In transplant patients, cPCs ≥0.165 % also predicted worse prognosis. Similarly, when considering cytogenetic risk factors in conjunction with cPC levels, comparable results were obtained. To evaluate whether the Revised International Staging System (R-ISS) groups could be further stratified based on different prognostic factors related to cPCs, our study revealed similar median PFS and OS rates in R-ISS II stage patients with cPCs ≥ 0.165% compared to those in the III stage (P=0.659 and 0.249, respectively).This study demonstrates that a high ratio of cPCs serves as a reliable indicator for predicting a poorer prognosis in MM cases. Furthermore, incorporating the R-ISS system and cytogenetic risk factors alongside the level of cPCs enhances the accuracy of prognostic predictions for patients with MM.